2007
DOI: 10.1590/s0004-27302007000200014
|View full text |Cite
|
Sign up to set email alerts
|

Doença cardiovascular no diabetes mellitus: análise dos fatores de risco clássicos e não-clássicos

Abstract: Cardiovascular disease, which includes coronary heart disease (CHD), cerebrovascular disease (CVD), and peripheral vascular disease (PVD), is the leading cause of mortality in populations, particularly in the diabetic one. Individuals with diabetes have at least a two-fold to four-fold increased risk of having cardiovascular events and a double risk of death compared with age-matched subjects without diabetes. A decline in mortality from CVD has been shown, but decline due to CHD is consistently lower in indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
11

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 88 publications
1
10
0
11
Order By: Relevance
“…In a review of literature it was observed that diabetic individuals had a three to four times greater risk of suffering a cardiovascular event and twice the risk of dying from this event than the general population 29 .…”
Section: Resultsmentioning
confidence: 99%
“…In a review of literature it was observed that diabetic individuals had a three to four times greater risk of suffering a cardiovascular event and twice the risk of dying from this event than the general population 29 .…”
Section: Resultsmentioning
confidence: 99%
“…However, the dynamics of living can be completely different when the level of education is higher, since patients with a higher level of education often have more job opportunities and higher salaries [17].…”
Section: Discussionmentioning
confidence: 99%
“…Acceleration of atherosclerosis in these patients can be due to insulin deficiency, defective insulin action, and hyperglycemia or associated metabolic defects [6]. Arterial hypertension and dyslipidemia frequently coexist with diabetes and contribute to the increased prevalence of CVD in diabetic patients [7-9]. The impact of some of these metabolic factors may be amplified by the presence of hyperglycemia.…”
Section: Introductionmentioning
confidence: 99%